Rumah Sakit Pendidikan Kampus II Universitas Negri Malang Dengan Pendekatan Green Hospital - Ihsanuz Zikra (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
The current lack of hospital health facilities in Indonesia with the ratio of the number of beds to the population in Indonesia is 1.21 beds per 1000 population, where WHO recommends 3 beds per 1000 population. In this regard, the State University of Malang wants to realize a Faculty of Medicine. By P KKI No. 12 of 2013 concerning the Implementation of the Indonesian National Qualifications Framework, one of the requirements is to have a teaching hospital. This hospital was designed with a Green Hospital approach which takes into account the principles of sustainable health and the environment in the design, operation, and maintenance processes aimed at protecting and managing natural resources and the quality of the environment in the future. In designing a hospital with a green hospital approach, the focus is on architectural aspects consisting of appropriate land development, energy efficiency, water conservation, materials, environmental health and comfort, healing gardens, and also environmental management. With the Green Hospital approach, the Teaching Hospital Campus II, State University of Malang, is expected to protect and care for the surrounding environment and also hospital patients in the treatment process with green hospital methods and criteria which create a space for hospital residents to be more comfortable both in the treatment process, learning, and also the treatment process with all hospital facilities.